A 2D Stationary FEM Model for Hydrocarbon Fuelled SOFC Stack Layers. (2nd June 2015) - Geisler, Helge; Dierickx, Sebastian; Weber, André; Ivers-Tiffée, Ellen
Abstract : In this study, the established model framework, where the physically coupled processes (i) charge-transfer chemistry, (ii) electron and ion conduction and (iii) gas species transport in the porous electrodes for hydrogen operation are implemented, is extended to predict local gas composition and electrochemical performance of hydrocarbon fuelled SOFC stack layers. The model geometry represents a 2D longitudinal section through a stack layer along the gas channel length. Consequently, the existing isothermal model framework is extended to meet the new requirements: (i) pressure driven gas transport in the gas channels is modeled by Navier-Stokes equations and in the porous electrodes by Darcy's law, (ii) all existing and new gas transport equations are extended to six gas species and (iii) global reaction equations for steam reforming and water-gas shift reaction are added. The model predicts (i) where gas diffusion limitations lead to drastic performance loss and (ii) where the Ni/8YSZ anode structure most likely will suffer severe damage.